Filsafat Etika dalam Islam: Antara Akhlak dan Hikmah - Agustianda, Agustianda (UIN Sumatera Utara, 2025)
Islamic ethics has unique characteristics that distinguish it from other ethical systems, because it is rooted in divine revelation while also making room for the role of reason. Two key concepts that stand out in Islamic philosophy of ethics are morality and wisdom. Morality is understood as a system of values and behaviors that is based on the Qur'an and Sunnah, and reflects the normative and spiritual aspects of Islamic teachings. Morality emphasizes character formation that reflects faith through behaviors such as honesty, patience, and justice. On the other hand, wisdom, which literally means wisdom, is a form of rational and spiritual intelligence that allows individuals to apply moral values precisely, contextually, and proportionally. This paper aims to explore the philosophical relationship between morality and wisdom in the Islamic ethical system. Morality provides a fixed and universal moral direction, while wisdom provides flexibility in the application of these values in the midst of the complexities of real life. In the contemporary context, this blend is essential to form a Muslim personality who is not only spiritually devout, but also intelligent in attitude, adaptive to change, and able to navigate global ethical challenges. Thus, Islamic philosophy of ethics does not clash between revelation and reason, but instead integrates them in a balanced form of moral praxis. This study emphasizes that morality and wisdom are the two main pillars in building a just, civilized, and highly aware society of human values.